In vitro propagation of Andrographis paniculata Nees.-A threatened medicinal plant of Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2016)
An efficient protocol was developed for in vitro regeneration of plantlets from shoot tip and nodal segment explants of Andrographis paniculata Nees. Nodal segment explants produced the highest number of shoots (18±1.24) when they were cultured on MS supplemented with 11.10 ?M/l BAP. Addition of 10% coconut water and 2.0 g/l activated charcoal to the above mentioned medium increased the number of shoots (30) per culture. Shoot tip explant also showed better performance in the same medium. Addition of 100 mg/l urea and 2.0 g/l activated charcoal to the medium showed proper shoot elongation. The isolated shoots rooted well (90%) on half-strength MS fortified with 9.80 ?M/l IBA, where average number of roots per shoot was 28-30. The plantlets were acclimatized successfully in poly bags containing a mixture of soil, sand and compost in 2:1:1 ratio. Finally acclimatized plantlets were transferred to experimental field.Jahangirnagar University J. Biol. Sci. 3(1): 67-73, 2014 (June)